Financial feasibility of investing in bulk soybean infrastructure: the case of an Evergreen Seed Agent - Huls, Bethany (Kansas State University, 2018)
For an Evergreen Seed Agent, making the financial decision to invest in bulk infrastructure is a large capital investment and requires a great deal of considerations. This thesis determines the soybean sales volume required for an investment in bulk soybean infrastructure to become financially feasible. A total of 1,456 soybean sales data points were used to run a regression model. Based on the results of the regression model, a correlation was determined between those agents that have bulk soybeans and soybean sales growth in comparison to those agents that did not have bulk soybeans. A “Bulk Soybean Decision Tool” was constructed and demonstrates costs and earnings of an Evergreen Seed Agent over a five-year period. The financial feasibility analysis concluded that the soybean volume required to consider investing in bulk soybeans is 8,488 units. In addition to a break-even analysis, three other base year volume scenarios were demonstrated. At the 3,233 unit base soybean sales volume, it is not financially feasible to invest in bulk. At the 10,265 unit base soybean sales volume, it is finically feasible to invest in bulk soybeans. Lastly, at the 18,912 unit base soybean sales volume, it is finically feasible to invest in bulk soybean infrastructure. The capabilities of the “Bulk Soybean Decision Tool” are significant for any Evergreen Seed Agent considering investing in bulk soybean infrastructure. Ensuring that an Evergreen Seed Agent is making a sound financial investment in bulk soybean infrastructure will allow for an increased adoption in infrastructure, resulting in increased soybean sales volume across the distribution network.
Keywords: Infrastructure; Investment; Distribution Network; Decision Tool; Agriculture